Trial stabilisation of running biomechanics with shoe familiarisation in trained distance runners - Gittoes, M.; Moore, I. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Appropriate trial sizes for biomechanical studies examining running shoe functionality are important to ensure valid insights into injury prevention strategies. The study aimed to examine the influence of shoe familiarisation on trial stabilisation in trained distance runners. A sequential averaging analysis was used to define trial stabilisation of biomechanical measures obtained from two testing conditions (new shoe and familiarised shoe). Between condition group analyses suggested similar trial stabilisation irrespective of shoe familiarisation (group mean ±SD: new: 7.5 ±2.0 trials; familiarised: 7.0 ±2.0 trials). Within group analyses identified variations in trial stabilisation according to the participant, condition and measure. An eight trial protocol was advocated for participantcondition analyses in longitudinal studies examining shoe functionality.